(3LOGhd aj eYQaI GdJGQjN GdYQHi hGdQhei hGdaGQSis ((3HdOI GdSeGf s)
(3ChdgG (B:s
(3jHOC HLOhd GdCjGe GdeQahYI s
(3BNQgG (B:s
(3hdcf HTQW edGMXI GdcHjSjI ai KhGfi GdYQHjI JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3HgG fXGe GdJYbjHIs
(3HBNQg ahGFO aiYde GdRGjLIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdeLGejYs